2022
DOI: 10.1155/2022/7264343
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Application Value of Different Esophagography Techniques in the Diagnosis of H-Type Tracheoesophageal Fistula in Neonates

Abstract: Objective. The study aimed to analyse the detection rates of the triple-lumen double-balloon catheter technique and conventional esophagography in diagnosing H-type tracheoesophageal fistula (H-TEF) in neonates. Methods. The data of 8 neonates diagnosed with H-TEF by surgery in the researchers’ hospital between January 2015 and January 2022 were collected. We compared the detection (true positive) rates of H-TEF by the triple-lumen double-balloon catheter technique, conventional esophagography, and multidetect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…H-type TEF accounts for about 5% of all trachea-esophageal malformation, with an estimated incidence of about one per hundred thousand live birth. 4 The early diagnosis of this defect is challenging 5 and can be delayed because the presentation is non-specific. 6 However, if diagnosed early, the approach to airway management and invasive ventilation before surgical correction is quite challenging, particularly with the significant defect.…”
Section: Introductionmentioning
confidence: 99%
“…H-type TEF accounts for about 5% of all trachea-esophageal malformation, with an estimated incidence of about one per hundred thousand live birth. 4 The early diagnosis of this defect is challenging 5 and can be delayed because the presentation is non-specific. 6 However, if diagnosed early, the approach to airway management and invasive ventilation before surgical correction is quite challenging, particularly with the significant defect.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%